A comparative biophysical and in-silico studies on the interactions of ticlopidine hydrochloride with two serum albumins. (April 2019) - Khatun, Samima; Riyazuddeen,; Rabbani, Gulam
Highlights: Tic quenches the fluorescence spectra of HSA and BSA in a static manner. Hydrogen bonding and/or van der Waals forces are responsible for complex formation. Tic binds site I (subdomain IIA) of HSA as well as BSA. Tic stabilized the native structure of HSA and BSA as revealed by CD spectroscopy. Amino acids for Tic binding to HSA and BSA are confirmed by molecular docking. Abstract: The current study is undertaken to explore the interaction between ticlopidine hydrochloride (Tic) and the serum transport proteins, human serum albumin (HSA) and bovine serum albumin (BSA) by multi-spectroscopic, calorimetric, and molecular modeling techniques. The fluorescence results indicate that quenching of HSA and BSA is initiated by Tic through static manner. The binding constant (Kb ) was found to be in the order of 10 4, reflecting high affinity of Tic for serum albumins. The binding site of Tic on HSA and BSA is determined by site specific displacement studies. The thermodynamic profile, obtained from isothermal titration calorimetry (ITC), suggested that all reactions are exothermic and hydrogen bonding and/or van der Waals are predominant forces in stabilizing the HSA-Tic and BSA-Tic complexes. The UV–vis, synchronous and 3D fluorescence spectroscopic results confirm conformational alteration in HSA and BSA by Tic which is further proved by CD spectroscopy. In addition, molecular docking on HSA-Tic and BSA-Tic systems were performed to confirm the binding site, amino acids residues involved in the binding process and their mode of interaction with Tic molecule. This study is expected to provide greater pharmacological understanding of Tic and highlights its pharmacokinetic properties.